Basic guide to infection prevention and control in dentistry - Pankhurst, Caroline; Coulter, Wilson (Basic guide to dentistry series., 2017)
Thoroughly updated, this new edition ensures all members of the dental team are up to speed on the practical aspects of infection prevention and control. It provides step-by-step guidance on the safe running of a dental practice, clear and concise explanations of the key issues and concepts, an overview of the evidence base, and coverage of legal and regulatory issues about which all staff members need to be aware.